PENGEMBANGAN EKONOMI KREATIF PESANTREN MELALUI USAHA TEPUNG MOCAF DAN ANEKA OLAHAN DARI SINGKONG DI PONDOK PESANTREN AL-HIDAYAH SUGIHWARAS PARENGAN TUBAN - Ulva Badi' Rohmawati; Ririn Fauziyah; Aya Mamlu'ah (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
The purpose of this activity is to equip members of the pesantren community with the knowledge and skills needed to innovate in economic development, particularly by utilizing local assets such as cassava, which is processed into mocaf flour. The method used is Asset-Based Community Development (ABCD), Generally involves several key stages such as discovery (finding assets), dream (formulating dreams/goals), design (designing strategies), define (determining more specific goals), and destiny (implementing programs). The outcomes of the activity show an increase in the partners’ knowledge and skills in processing cassava into mocaf flour and other value-added products. Furthermore, an Entrepreneurship Team was formed, and there was an improvement in the local economy through businesses that can be marketed to the general public.